The teacher who forgot too much - Brezenoff, Steven; Canga, C. B. (Minneapolis, Minn. : Stone Arch Books, 2010)
Catalina Duran, who is known as Cat, goes to the recycling center with her class, and when they find out that the plant has been sabotaged, Cat and her friends try to save the day.
4.4
3-6
Keywords: School field trips -- Juvenile fiction; School field trips -- Fiction; Mystery and detective stories; Field trips -- Fiction; Mystery fiction; Mystery fiction